Limity důvěry. Bývalí vojáci Wehrmachtu ve službě u československého letectva v Británii za druhé světové války - Zdenko Maršálek (Theatrum Historiae)
The paper explores the trust limitations of the Czechoslovak exile authorities during World War II towards those volunteers of the Czechoslovak exile military forces who had formerly served in the Wehrmacht. It has come to light that they were not prohibited from joining even the elite of the armed forces represented by air force units. On the other hand, the given degree of mistrust is demonstrated by the fact that they were only assigned to the ground personnel. Moreover, men who had gone through flying personal training in the German Luftwaffe were never accepted to the exile air force units.